(untitled) (Global Journal of Human-Social Science, 2013)
The landmark 1967 Loving vs. Virginia Supreme Court ruling ended anti-miscegenation laws in America. However, the historic event did not change how interracial marriages were viewed from a societal standpoint (Alonso, 2000). Although such unions have increased in the 21st century, problems associated with acceptance still abound (Jayson, 2011). The purpose of this qualitative research study is to explore how faith impacts Black-White Christian marriages. Does it help these couples cope with adversity and/or handle daily struggles better than those who do not share the same beliefs? Or, is there no significant difference at all? William Gudykunst’s (1995) Anxiety-Uncertainty Management Theory will serve as a theoretical framework for the study. It contends the development of healthy interethnic relations and flexible interactions require a high degree of intergroup communication, and in the same vein, a heightened level of out-group communication (Matusitz, 2012). Ideas for further research will also be explored.